Sports Development Reforms - Rayimov Shakhzod Alikulovich (Zien Journals, 2023)
This article contains information about the sports sector in the Republic of Uzbekistan legal grounds for development and reforms in the field of physical education and sports in our country about.
Keywords: President's Cup; concept; sprouts of Hope